Investigation of Prolactin Receptor Activation and Blockade Using Time-Resolved Fluorescence Resonance Energy Transfer - Tallet, Estelle; Fernandez, Isabelle; Zhang, Chi; Salsac, Marion; Gregor, Nathalie; Ayoub, Mohammed A.; Pin, Jean-Philippe; Trinquet, Eric; Goffin, Vincent (Frontiers in Endocrinology, 2011)
The prolactin receptor (PRLR) is emerging as a therapeutic target in oncology. Knowledge-based drug design led to the development of a pure PRLR antagonist (Del1-9-G129R-hPRL) that was recently shown to prevent PRL-induced mouse prostate tumorogenesis. In humans, the first gain-of-function mutation of the PRLR (PRLRI146L) was recently identified in breast tumor patients. At the molecular level, the actual mechanism of action of these two novel players in the PRL system remains elusive. In this study, we addressed whether constitutive PRLR activation (PRLRI146L) or PRLR blockade (antagonist) involved alteration of receptor oligomerization and/or of inter-chain distances compared to unstimulated and PRL-stimulated PRLR. Using a combination of various biochemical and spectroscopic approaches (co-IP, blue native electrophoresis, BRET1), we demonstrated that preformed PRLR homodimers are altered neither by PRL- or I146L-induced receptor triggering, nor by antagonist-mediated blockade. These findings were confirmed using a novel time-resolved fluorescence resonance energy transfer (TR-FRET) technology that allows monitoring distance changes between cell surface tagged receptors. This technology revealed that PRLR blockade or activation did not involve detectable distance changes between extracellular domains of receptor chains within the dimer. This study merges with our previous structural investigations suggesting that the mechanism of PRLR activation solely involves intermolecular contact adaptations leading to subtle intramolecular rearrangements.